PENGEMBANGAN BAHAN AJAR FISIKA BERUPA BUKU BERBASISREACT (RELATING, EXPERIENCING, APPLYING, COOPERATING, AND TRANSFERRING) PADA PEMBELAJARAN FISIKA DI SMA - Rofiah Al Adawiyah; Albertus Djoko Lesmono; Sri Handono Budi Prihandono (FKIP Universitas Jember, 2018)
Abstract REACT (Relating, Experiencing, Applying, Cooperating, and Transferring) was one of teach model in contextualization proposed by Michael L. Crawford.Therefore, this research was focused on the development of teaching materials basedon REACT in learning physics for Senior High School. A product produced by thisresearch is the students’ book. The purpose of this study to determine the validity ofbook, describing effectiveness and student’s response after using teaching materialbased on REACT. The research used research and development (R&D) model with theprocedure claimed by Borg and Gall, which was modified into four phase, namely:1)research and information gathering, 2)planning, 3)development of initial design ofproduct,until 4)initial field experiment. Data result analyzed by descriptive qualitativemethod and quantitative descriptive. The results of this research indicates that theteaching materials based on REACT was very good with validity 90,02%. Meanwhile,teaching materials in the form of teaching material-based on REACT has mediumvalue N-Gain amount 0,69 ,but student gives good response with 84,41% positive toteaching materials based on REACT.Key word: teaching materials based on REACT, validity, effectiveness, response.